Quantitative analysis validation for sclerotherapy treatment of lower limb telangiectasias - Bertanha, Matheus [UNESP]; Mellucci Filho, Pedro Luciano [UNESP]; Genka, Caroline Araujo [UNESP]; de Camargo, Paula Angeleli Bueno [UNESP]; Grillo, Vinicius Tadeu Ramos da Silva [UNESP]; Sertório, Nathalia Dias [UNESP]; Rodrigues, Lenize da Silva [UNESP]; Sobreira, Marcone Lima [UNESP]; Lourenção, Pedro Luiz Toledo de Arruda [UNESP] (Elsevier, 2023)
Background: The evaluation of sclerotherapy efficacy for lower limb telangiectasias, which is the standard treatment for such condition, is commonly assisted by scores based on before and after pictures. This method is marked by its subjectivity, which impairs the precision of studies on the subject, making it unfeasible to evaluate and compare different interventions. We hypothesize that a quantitative method for evaluating the effectiveness of sclerotherapy for lower limb telangiectasias may present more reproducible results. Reliable measurement methods and new technologies may become part of the clinical practice in the near future. Methods: Before and after treatment photographs were analyzed using a quantitative method and compared with a validated qualitative method based on improvement scores. Reliability analysis of the methods was performed, applying the intraclass correlation coefficient (ICC) and kappa coefficient with quadratic weights (Fleiss Cohen), for analysis of inter-examiner and intra-examiner agreement in both evaluation methods. Convergent validity was evaluated by applying the Spearman test. To assess the applicability of the quantitative scale, the Mann-Whitney test was used. Results: A better agreement between examiners is shown for the quantitative scale, with a mean kappa of.3986 (.251-.511) for qualitative analysis and a mean kappa of.788 (.655-.918) for quantitative analysis (P <.001 for all examiners). Convergent validity was achieved by correlation coefficients of.572 to.905 (P <.001). The quantitative scale results obtained between the specialists with different degrees of experience did not show statistical difference (seniors: 0.71 [−0.48/1.00] × juniors: 0.73 [−0.34/1.00]; P =.221). Conclusions: Convergent validity between both analyses has been achieved, but quantitative analysis has been shown to be more reliable and can be applied by professionals of any degree of experience. The validation of quantitative analysis is a major milestone for the development of new technology and automated, reliable, applications.
Keywords: Computer-assisted; Evaluation methodology; Image processing; Sclerotherapy; Telangiectasias; Validation Study; Veins